Pengaruh e-service quality dan e-trust terhadap repurchase intention pada pengguna tiket.com di Surabaya - Salsabila, Ainan; Pudjoprastyono, Hery (Jurnal Riset Pendidikan Ekonomi, 2025)
The development of digitization-based technology in the business sector is indispensable and highly attractive. The quality of a product or service continues to be developed online through internet media. The research is intended to determine the effect of E-Service Quality and E-Trust on Repurchase Intention for Tiket.com users in Surabaya. The approach used is a quantitative approach. The population is Tiket.com users. While the research sample is Tiket.com users in Surabaya. The researchers determined the use of non-probability sampling techniques with purposive sampling techniques. Researchers used a questionnaire distributed to 130 respondents aged 17-35. The data obtained will be analyzed using Smart PLS 3.0. The results showed that E-Service Quality has a significant positive effect on Repurchase Intention, E-Trust has a significant positive effect on Repurchase Intention, and E-Service Quality and E-Trust have a significant positive effect on Repurchase Intention.